2011
DOI: 10.1002/syn.20943
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated methamphetamine induced neurotoxicity by modafinil administration in mice

Abstract: Methamphetamine (METH) is a highly addictive drug that might induce neurotoxicity. Clinical trials have reported that modafinil, a wake-promoting agent used to treat sleep disorders, may have some efficacy for the treatment of psychostimulant addiction. In this study we tested possible neuroprotective effects of modafinil after toxic METH administration in mice. We evaluated the effect of modafinil (two injections of either 90 or 180 mg/kg) and METH binge (3 × 7 mg/kg i.p. injections, 3-h apart) coadministrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 35 publications
(45 reference statements)
1
14
0
Order By: Relevance
“…Nevertheless, modafinil maintained its neuroprotective properties against METH-induced alterations in the striatum at different ambient temperatures. Results from the present study suggest that even under rather demanding environmental conditions (high or cold ambient temperatures) modafinil was still able to interfere with METH harmful effects as it was previously shown for METH-induced changes in biochemical markers (Raineri et al, 2011; 2012; Zolkowska et al, 2009) and behavioral functions (Zolkowska et al, 2009; Gonzalez et al, 2014, Reichel et al, 2014). Moreover, we found that modafinil (by itself) did not alter the level of any dopaminergic marker in the striatum even at high ambient temperatures.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Nevertheless, modafinil maintained its neuroprotective properties against METH-induced alterations in the striatum at different ambient temperatures. Results from the present study suggest that even under rather demanding environmental conditions (high or cold ambient temperatures) modafinil was still able to interfere with METH harmful effects as it was previously shown for METH-induced changes in biochemical markers (Raineri et al, 2011; 2012; Zolkowska et al, 2009) and behavioral functions (Zolkowska et al, 2009; Gonzalez et al, 2014, Reichel et al, 2014). Moreover, we found that modafinil (by itself) did not alter the level of any dopaminergic marker in the striatum even at high ambient temperatures.…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, modafinil enhances electrotonic coupling by increasing the effectiveness of gap junction communication between neurons (Urbano et al, 2007; Garcia-Rill et al, 2007). Interestingly, modafinil can also protect against METH-induced DA depletion and reductions in TH and DAT levels in the striatum (Raineri et al, 2011). Furthermore, modafinil also attenuated METH-induced hyperthermia and glial activation in striatal tissue (Raineri et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, modafinil enhances electrotonic coupling by increasing the effectiveness of gap junctions between neurons (Urbano et al, 2007; Garcia-Rill et al, 2007). We also demonstrated that modafinil can protect against METH toxicity (Raineri et al, 2011; 2012). Specifically, modafinil was able to prevent METH-induced toxic effects that included DA depletion and reductions in tyrosine hydroxylase (TH) and DAT levels in the striatum (Raineri et al, 2011).…”
Section: Introductionmentioning
confidence: 58%
“…We also demonstrated that modafinil can protect against METH toxicity (Raineri et al, 2011; 2012). Specifically, modafinil was able to prevent METH-induced toxic effects that included DA depletion and reductions in tyrosine hydroxylase (TH) and DAT levels in the striatum (Raineri et al, 2011). Furthermore, modafinil also attenuated METH-induced hyperthermia, glial activation, and increased expression of proapoptotic proteins (Raineri et al, 2012).…”
Section: Introductionmentioning
confidence: 58%